The Effectivieness of Group Counseling Using The Solution Focused Brief Therapy (SFBT) Approach to Improve The Altruistic Behavior of Studients of State Middle School 6 Probolinggo - Firania Jaya Dininggar; Leny Latifah; Devi Permatasari (Ilmina: Journal of Education and Counseling, 2025)
Altruism is a specific form of behavioral adjustment aimed at the benefit of others, tending towards self-harm, and driven by the desire to improve the welfare of others without expecting anything in return. The SFBT approach is a therapy that builds on the client's strengths, enabling them to identify and resolve their own problems. The purpose of this study was to determine the effectiveness of group counseling using the SFBT approach in improving altruistic behavior in eighth-grade students at SMPN 6 Probolinggo. The method used in this study was a one-group pretest-posttest design. The sampling technique used was purposive sampling, meaning the sampling method was based on specific considerations. The subjects were five students from class VIIIC of SMPN 6 Probolinggo, obtained from the pretest results to improve altruistic behavior. The instrument used in this study was the altruistic behavior scale. Data analysis in this study used parametric statistics with a paired-sample t-test, processed using SPSS 22.0 for Windows. The results of the study are described as follows: (a) the level of altruistic behavior of class VIIIC students of SMPN 6 Probolinggo who were the subjects of the study before being given group counseling treatment with the SFBT approach was in the "low" category, the average pre-test score of the altruistic behavior scale was 62.4. (b) the level of altruistic behavior of class VIII students of SMPN 6 Probolinggo who were the subjects of the study after being given group counseling treatment with the SFBT was in the "high" category, the average post-test score of the altruistic behavior scale was 127.8. (c) the results of the paired sample t-test analysis from the calculation results can be concluded that the sig value (-2 tailed) is 0.001 <0.05, so HO is rejected so it can be concluded that it is effective in reducing the altruistic behavior of students of SMPN 6 Probolinggo.